Dehesa ecosystem: Production and preservation - Olea L.; Viguera F.J. (Dynamics and sustainability of Mediterranean pastoral systems, 1999)
The dehesa is an ecosystem in which species of herbs, bushes and trees coexist in a semi-desert regime, contributing to the feeding of domestic and wild animals. The improvement and exploitation of these agro-sylvopastoral systems must be founded on the principles of preservation of the environment and the idea of creating systems that can be maintained with a correct usage of natural resources. Fertilization of the natural pastures, the introduction of a new pasture species and varieties, the favouring of the species of bush that have a forage value and the preservation of the arboreous stratum are methods which will allow us to preserve this ecosystem.
9. Meeting of the Mediterranean Sub-Network of the FAO-CIHEAM Inter-Regional Cooperative Research and Development Network on Pastures and Fodder Crops, 1997/11/26-29, Badajoz (Spain)